The Effect of Cerebellar Transcranial Direct Current Stimulation on A Throwing Task Depends on Individual Level of Task Performance. (10th February 2018) - Mizuguchi, Nobuaki; Katayama, Takashi; Kanosue, Kazuyuki
Highlights: Participants practiced dart throwing while receiving a 2-mA cerebellar tDCS. Anodal, cathodal, and sham-tDCS were conducted with cross-over design. The effect of cathodal tDCS was correlated with individual dart performance. Cathodal tDCS facilitated learning of dart only in individuals with low performance. Abstract: The effect of cerebellar transcranial direct current stimulation (tDCS) on motor performance remains controversial. Some studies suggest that the effect of tDCS depends upon task-difficulty and individual level of task performance. Here, we investigated whether the effect of cerebellar tDCS on the motor performance depends upon the individual's level of performance. Twenty-four naïve participants practiced dart throwing while receiving a 2-mA cerebellar tDCS for 20 min under three stimulus conditions (anodal-, cathodal-, and sham-tDCS) on separate days with a double-blind, counter-balanced cross-over design. Task performance was assessed by measuring the distance between the center of the bull's eye and the dart's position. Although task performance tended to improve throughout the practice under all stimulus conditions, improvement within a given day was not significant as compared to the first no-stimulus block. In addition, improvement did not differ among stimulation conditions. However, the magnitude of improvement was associated with an individual's level of task performance only under cathodal tDCS condition ( p < 0.05). This resulted in a significant performance improvement only for the sub-group of participants with lower performance levels as compared to that with sham-tDCS ( p < 0.05). These findings suggest that the facilitation effect of cerebellar cathodal tDCS on motor skill learning of complex whole-body movements depends on the level of an individual's task performance. Thus, cerebellar tDCS would facilitate learning of a complex motor skill task only in a subset of individuals.